App atmospherics, personality factors and technology acceptance behaviour towards the adoption of mobile banking apps – a systematic literature review - Behera, Mukti Prakash (2023)
Mobile banking apps have become increasingly popular in recent years, providing customers with a convenient and secure way to manage their finances. These apps have transformed the way we conduct financial transactions and have revolutionized the banking industry. However, despite the widespread adoption of mobile banking apps, there is still a significant gap in our understanding of the factors that influence customers' acceptance of these apps. This systematic literature review aims to provide a comprehensive overview of the current state of research in this area based on app atmospherics, personality factors, and technology acceptance behaviour. The review analysed 40 papers published between 2019 to 2023 to synthesize the evidence and identify key factors that influence the adoption and intention to use mobile banking apps. One of the key findings of the review is that app atmospherics, including the visual design, functionality, and interactivity of mobile banking apps, significantly influence customers' technology acceptance behaviour. Customers are more likely to adopt mobile banking apps that are visually appealing, user-friendly, and interactive. Additionally, technology acceptance behaviour, such as perceived usefulness, perceived ease of use, and perceived trustworthiness, also plays a crucial role in shaping customers' attitudes towards mobile banking apps. The review also identified personality factors such as emotions and attitudes that significantly influence the adoption and intention to use mobile banking apps. Customers who are open to change, innovative, and willing to take risks are more likely to adopt mobile banking apps than those who are not. Additionally, customer demographics, cultural differences, and technological advancements were identified as key factors that affect the adoption of mobile banking apps.  Banks and financial institutions must keep up with technological advancements to stay ahead of the competition and provide customers with the latest and most innovative technologies. This study has identified the key research gaps and suggest a theoretical framework for future research agenda.